THU0311 Fecal microbiota in behÇet's syndrome patients with mucocutanous and uveitis involvement. (15th June 2017) - Tecer, D; Gogus, F; Kalkancı, A; Erdogan, M; Coban, S; Hasanreisoglu, M; Karakan, T
Abstract : Background: Innate immunity has a major role in the pathogenesis of Behçet's syndrome. The gut microbiota is an active component of the immune system. It plays an important role in the formation of the immune system in the early life and in the continuation of immune homeostasis through the life. Dysbiosis, imbalance in the gut microbiota, can lead to many serious metabolic and inflammatory pathologies Objectives: We aimed to investigate the gut microbiota structure in Behçet's syndrome patients with mucocutanous and uveitis involvement only. Methods: 6 patients with Behçet's syndrome with uveitis, 12 patients with familial Mediterranean fever (FMF) and 9 patients with Crohn's disease (CD) and 10 healthy controls were included. Patients, positive and healthy controls were excluded if they had one of the following combined diseases/situations: a) gastrointestinal surgical history (e.g. bariatric surgery, gastrectomy or colectomy), b) antibiotic or probiotics use in the last 3 months, c) specific dietary restriction, d) malignancy, e) additional autoimmune disease or inflammatory bowel disease. Total DNA was extracted from fecal samples using the QIAamp DNA stool Mini Kit following the manufacturer's instructions (Qiagen). Next generation sequencing of 16SrRNA gene was performed using Ion Torrent Technology. Partial 16S rRNA ene sequences were amplified from extracted DNA using the 16S Metagenomics Kit (Life Technologies). The integrity of the PCR amplicons was analyzed by gel electrophoresis. PCR products were purified using AMPure XP DNA purification beads and Invitrogen DynaMaq magnet apparatus. DNA concentration of the amplified sequence was equalized through the Qubit System (Life Technologies). The libraries was created by using the Ion Plus Fragment Library Kit. Barcodes were also added to each sample using the Ion Express Barcode Adapters Kit. Emulsion PCR was carried out using the Ion One Touch 2 machine. Sequenciing of the amplicon libraries was carried out on a 318 chip the Ion Torrent Personal Genome Machne System and Ion PGM Hi-Q kit. 16S rRNA sequences were analyzed by Ion Reporter Software. Results: In healthy subjects, fecal microbiota consisted predominatly of Bacteroidetes (53.2%) including Bacteroides and Prevotella genuses. Firmicutes such as Bacilli, Clostridia, followed, consisting 31.2% of the bacterial community. Fecal bacterial flora of patients with Behçet's syndrome consisted of Firmicutes (45%), Proteobacteria (23%) such as Enterobacteriaceae and Prevotellaceae, and Bacteriodetes (10%). FMF cases were found to be colonized by Firmicutes (39.3%), Bacteriodetes (32.2%) and Proteobacteria (13.6%) predominantly. CD cases were colonized by Enterobacteriacea (43%), and other Proteobacteria groups, followed by Bacteriodetes (15.4%) and Firmicutes (8.8%). Conclusions: Fecal flora of patients with Behçet's syndrome and of positive control groups (FMF and CD) differed significantly from that of healthy controls. In a subgroup of patients with Behçet's disease with uveitis and muscucutaneaous involvement only, firmicutes species seem to be the dominant bacterial fecal flora. Disclosure of Interest: None declared